Efeitos da exposição materna ao Triclosan, durante a prenhez e lactação, no desenvolvimento físico, sexual inicial e função testicular da prole masculina de rato - Machado, Camila Stacheski (2016)
The triclosan (TCS) is a bactericidal agent widely used in personal hygiene products, in the context of odontology, this substance has been showing itself efficient in reducing the dental plaque and gingivitis, besides controlling the progression of periodontal disease. However, it's questionable the real benefits of using the TCS in large scale in different products, once this compound has been included on the list of endocrine disrupters. The growing observation of the prevalence of environmental contaminant with properties for the endocrine disrupting has been generating a considerable debate between the scientists, regulatory agencies and general public, about the potential risks which these substances represent to the man's and animal's productive health. Many of these compounds are present in our daily routine. The objective of this study was to evaluate the effects resulted from the exposure to TCS bactericidal, during pregnancy and lactation of mother rats, on the physical development, initial sexual and testicular function of the male son on the following phase of the development: puberty and sexual maturity. For this, 16 rats Wistarprenhes were used, separated in four experimental groups, with 4 animals each one: GI- received corn oil daily by gavage; GII - received TCS, at a dose of 75 mg/kg/day. GIII- received TCS, at the dose of 150 mg/kg/day and GIV - received TCS, at the dose 300 mg/kg/day. The rats where weighed in alternate days throughout the experimental period, to the adjustment of the dose and monitored about the birth of the offspring. At birth, the offspring was weighed and evaluated about the initial physical development: age of the ears' detachment, hair onset, and eruption of incisors and eyes opening. The male offspring were kept and monitored about the external physical parameter of initial sexual development (descended testicles age and prepuce separation). When they're 60 (puberty) days and 90 (sexual maturity) years old, they were weighed and sacrificed to the organs collecting and weighing and histological analysis of the spermatogenesis stages and Sertoli cells counting. The results showed that the gain of body weight of the female rats during the pregnancy was similar to the experimental groups. However, there was a body weight-loss in the end of the experimental period, of the rats of group GIV in comparison to 14 group GI. The pregnancy average time and size of the offspring were similar between the groups. The average weigh of the offspring treated with TCS, in different doses was smaller (p<0,05), in comparison to group GI. The initial physical development and the descended testiscles were similar between the experimental groups. The offspring exposed to TCS, during pregnancy and lactation, it was observed a delay (days) on the prepucial separation. In puberty (60 days), it was observed a meaningful weight-loss of the seminal gland on groups GIII and GIV, in comparison to group GI. When they were 90 days old, it was observed liver weight-loss and a weight gain of the prostate of the animals of group GIV, in comparison to the animals of group GI. The analysis of the stages of the seminiferous epithelium cycle of the 60 days animals showed an increase of the stages I-VI on the animals treated with TCS 300mg/kg/day in comparison to group GI (p<0,01). The 90 days animals showed an increase of the stages VII-VIII, IX-XIII and decrease on the frequency of the stage XIV of the animal spermatogenesis treated with different doses of TCS when compared to group GI (p<0,01). There was no difference on the number counting of Sertoli cells between the animals of the different experimental groups. We concluded that the maternal exposition to TCS during the gestation period and lactation causes on the male offspring, intrauterine development restriction, delay on the puberty installation, change the weight of the seminal gland in animals at 60 days, as well, changes in liver weight and prostate in animals with 90 days, and disrupting the seminiferous epithelial cycle in both age.